Triple Crossover Study on Absorption and Excretion of Ampicillin, Pivampicillin, and Amoxycillin - Verbist, L. (1974)
The absorption and excretion of equivalent doses of ampicillin, pivampicillin, and amoxycillin were compared in 10 healthy volunteers after administration of these antibiotics in a randomized triple crossover fashion. As recommended, ampicillin and amoxycillin were administered on an empty stomach, whereas pivampicillin was given with breakfast. The mean half-life times were nearly identical for all three antibiotics: 60.9 min for ampicillin; 58.4 min for pivampicillin; and 62.2 min for amoxycillin. The absorption of the drugs was evaluated according to the following three criteria: the mean peak serum levels; the “area under the curve”; and the percentage of recovery in urine. By these criteria, pivampicillin was the best-absorbed drug, with absorption 3.0 to 3.6 times higher than that of ampicillin and 1.2 to 1.5 times higher than that of amoxycillin, whereas the absorption of amoxycillin was 2.1 to 2.9 times higher than that of ampicillin.